Factors Affecting the Level of the Quality of Life of the Elders in the network Elderly School of Muang District, Muang District, Phrae Province -ปัจจัยที่มีผลกับระดับคุณภาพชีวิตของผู้สูงอายุในโรงเรียนผู้สูงอายุในเครือข่ายอำเภอเมืองแพร่ จังหวัดแพร่ - Patpong, Pichet ((PMJCS) Phrae Medical Journal and Clinical Sciences, 2018)
Background: Thailand is going on the beginning of Aging society. In 30 year from now, the number of the elder will be increased to 17.7 M peoples approximately. From this effect, It will be caused economic, Society,physical health, mentality’s terrible andincrease the ratio of elderly. The establishment of the network elderly school is came from the concept of long term care concept cause was changing of population trends focus on elderly care, Learn as the group format, Leisure activities and the art of local wisdom. The researcher sees the benefits of the network elderly schools are several advantages and limitations. They are affecter the quality of the elderly as a whole, So this information will be a one of guidance for long-term care management sustainability and Longevity. Objective: To the level of the quality of life of elders in the network elderly school of Muang District, Muang District, Phrae Province and to study personal factors such as sex, age, occupation, coexistence of families and disease. Social and economic variables such as the income, group membership and year of activities in elderly school was affecting the level of the physical quality, mental quality and social quality. Study design: This study is descriptive study. The sample consisted 247 elders in network elderly school ofMuang District were serected by purposive sampling to the level of quality of elderlys in network elderly school of Muang District were affecting the level of quality for 12 weeks (April to June 2017). Results: The relationship between the personal factors that age, occupation , disease, coexistence of families had not statistically significant relationship and physical, mental, social and all quality of life of elders in the network elderly school. And found sex variables had statistically significant relationship between men, women and mental quality. Disease variables found had statistically significant relationship and physical and social quality. The income had not statistically significant relationship and physical, mental, social and all quality of life of elders. And finally this study found statistically significant relationship between a year of activities in elderly school and the level of physical, mental and all quality of life, but no significant relationship with the level of the social quality of life. Conclusions: Based on result found sex, disease and illness were related to quality of life. So the activities of the elderly school should be varied and based on the gender of the elderly. Focus on health activities and supplement activities that are beneficial to health, body, mind and society more. Keywords: Elderly, Elderly school, Elderly school of Muang District, Muang, Muang District, Phrae Province